2012
DOI: 10.1891/0886-6708.27.6.957
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Social Reactions to the Victim in a Hypothetical Sexual Assault Scenario: The Role of Victim and Perpetrator Alcohol Use

Abstract: College students' responses to a hypothetical sexual assault scenario involving alcohol use by the victim and/or perpetrator were examined (N = 295). Participants reported on victim/perpetrator responsibility, the extent to which the scenario would be considered rape, and their likelihood of providing positive or negative responses to the victim. Compared to women, men indicated that they would provide more negative and less positive social reactions to the victim, were less likely to identify the scenario as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 47 publications
3
20
2
Order By: Relevance
“…All of these differences may contribute to social reactions women receive from others..Prior research suggests that that alcohol-specific social reactions, will likely benegative. In experimental studies using sexual assault scenarios, people are more likely to blame survivors and hold them responsible when presented with information that survivors had been drinking (Cameron & Strizke, 2003; Norris & Cubbins, 1992; Richardson & Campbell, 1982; Schuller & Stewart, 2000; Sims, Noel, & Maisto, 2007; Stormo, Lang, & Stritzke, 1997; Untied, Orchowski, Mastroleo, & Gidycz, 2012). Victim blame partly depends on the perpetrators’ alcohol use.…”
mentioning
confidence: 99%
“…All of these differences may contribute to social reactions women receive from others..Prior research suggests that that alcohol-specific social reactions, will likely benegative. In experimental studies using sexual assault scenarios, people are more likely to blame survivors and hold them responsible when presented with information that survivors had been drinking (Cameron & Strizke, 2003; Norris & Cubbins, 1992; Richardson & Campbell, 1982; Schuller & Stewart, 2000; Sims, Noel, & Maisto, 2007; Stormo, Lang, & Stritzke, 1997; Untied, Orchowski, Mastroleo, & Gidycz, 2012). Victim blame partly depends on the perpetrators’ alcohol use.…”
mentioning
confidence: 99%
“…Another explanation for why no effect of complainant intoxication was found on complainant credibility or blame is the absence of a no alcohol condition in this study. Previous studies which have found an effect of complainant intoxication on complainant blame have used no alcohol conditions, where the complainant does not drink at all, with the largest differences in complainant blame observed between no alcohol and alcohol conditions (e.g., Untied et al, 2012;A. M. Wall & Schuller, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of first victimization of completed rape (defined as forced penetration and completed alcohol-or-drug-facilitated penetration) among females is 78.7% occurring before the age of 25 years, with 38.3% of completed rapes occurring during the age associated with college, 18-24 years (Black et., 2011). Supporting the NISVS data, various studies have shown that more than one in four college women report being forced to have sexual intercourse at some point in their lifetimes (Gidycz, Orchowski, King, & Rich, 2008;Gross, Winslett, Roberts, & Gohm, 2006;Untied, Orchowski, Mastroleo, & Gidycz, 2012). The estimated sexual violence reported by men is lower than that experienced by women.…”
Section: Introductionmentioning
confidence: 84%